The Effect of Transparency and Accountability on The Quality of Village Financial Reports (Empirical Study in Paseh District, Sumedang District) - Sukmayadi Sukmayadi; Ading Rahman Sukmara (CV. Ulil Albab Corp, 2024)
This research aims to determine the influence of transparency and accountability on the quality of village financial reports in Paseh District, Sumedang Regency. The case study in this research is a village official who is tasked with managing village financial reports. The method in this research uses quantitative research methods with survey methods. Data collection was carried out using a cluster random sampling technique by distributing questionnaires to 72 respondents as a sample. The data analysis techniques used in this research are normality test, multiple linear regression test, partial correlation test, coefficient of determination test, hypothesis test t test (partially), f test (simultaneously) using the IBM SPSS Version 25 program. Research Results These are: (1) Transparency has a positive and significant effect on the Quality of Village Financial Reports, with a regression coefficient of 0.323, a Determination Coefficient of 0.351 or 35.1%, a value of t-count>t-table (2.487>1.66724) with a value significant 0.015<0.05. (2) Accountability has a positive and significant effect on the Quality of Village Financial Reports, with a regression coefficient of 0.472, a Determination Coefficient value of 0.427 or 42.7%, a t-count>t-table value (4.018>1.66724) with a significant value of 0.000 <0.05. (3) Transparency and Accountability have a positive and significant effect on the Quality of Village Financial Reports. With a Determination value of 0.466 or 46.6% and with a F-count>F-table value (32.023>3.98> with a significant value of 0.000<0.05, this means that the influence of Transparency and Accountability has a significant positive effect on the Quality of Village Financial Reports in Paseh District, Sumedang Regency